1979
DOI: 10.1017/s0140525x00061926
|View full text |Cite
|
Sign up to set email alerts
|

Brain mechanisms for offense, defense, and submission

Abstract: A preliminary attempt is made to analyze the intraspecific aggressive behavior of mammals in terms of specific neural circuitry. The results of stimulation, lesion, and recording studies of aggressive behavior in cats and rats are reviewed and analyzed in terms of three hypothetical motivational systems: offense, defense, and submission. A critical distinction, derived from ethological theory, is made between motivating stimuli that simultaneously activate functional groupings of motor patterning mechanisms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
9

Year Published

1980
1980
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(78 citation statements)
references
References 255 publications
(192 reference statements)
1
67
1
9
Order By: Relevance
“…A motivation with security as its goal is not among the five special motivations recognized classically in psychology, which are hunger, pain, sex, maternal, and exploratory motivations (Hebb, 1966). However, ethologically oriented psychologists (e.g., Adams, 1979;Bolles & Fanselow, 1980;Gilbert, 1989;Marks & Nesse, 1994;Masterson & Crawford, 1982;Trower, Gilbert, & Sherling, 1990) have advanced the notion of a motivationally fundamental "defense system" concerned with the detection and amelioration of both physical and social potential threats to security. In general terms, motivation refers to the tendency of the whole organism to be active in a selective and organized way, and special motivation refers to that tendency that is also biologically primitive and necessary for species survival (Hebb, 1966).…”
Section: A Reconceptualization Of Ocd In Terms Of Motivationmentioning
confidence: 99%
“…A motivation with security as its goal is not among the five special motivations recognized classically in psychology, which are hunger, pain, sex, maternal, and exploratory motivations (Hebb, 1966). However, ethologically oriented psychologists (e.g., Adams, 1979;Bolles & Fanselow, 1980;Gilbert, 1989;Marks & Nesse, 1994;Masterson & Crawford, 1982;Trower, Gilbert, & Sherling, 1990) have advanced the notion of a motivationally fundamental "defense system" concerned with the detection and amelioration of both physical and social potential threats to security. In general terms, motivation refers to the tendency of the whole organism to be active in a selective and organized way, and special motivation refers to that tendency that is also biologically primitive and necessary for species survival (Hebb, 1966).…”
Section: A Reconceptualization Of Ocd In Terms Of Motivationmentioning
confidence: 99%
“…In this study, the resident-intruder model is used to elicit aggression, either attack or defense behavior, in an interactive dyadic encounter, when the resident initiates attacks against the intruder [22][23][24][25][26]. The competition for food will further aggravate the levels of aggression that strongly resemble the natural situation in which animals establish and defend territories or compete for food to survive in the social group.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, in our study rearing conditions were similar for all the mice, and, moreover, we measured aggression levels as attack latency scores, thereby avoiding actual fighting. With regard to age, it has been reported that only sexually mature intruders appear to elicit attack by mature males (Thor & Flannelly 1976b), which may be related to the androgen-dependence of the attack-eliciting properties of intruders (Thor & Flannelly 1976a;Adams 1979). The intruders used in the present study were ofsimilar age, but baseline plasma testosterone levels differ between the two lines (with the SAL line having the higher levels; Van Oortmerssen et al 1987).…”
Section: Discussionmentioning
confidence: 70%